The Role of Entrepreneurial Strategy-Making Dimensions towards Internet Business Performance in Malaysia - Adam, Sabrinah; Mahadi, Batiah (International Journal of Engineering and Technology, 2018)
Internet business today is facing major transformations due mainly to increased competition, changes in consumer behaviour, and technological advancements. As Internet business is an important growth engine in Malaysia nowadays, a potential of a good entrepreneurial strategy-making (ESM) can be discovered to develop Malaysian Internet business. Besides, ESM is recognised as the driver of growth and profitability. Thus, this paper aims to develop a conceptual framework related to the role of ESM dimensions, which is the role of innovativeness, proactiveness and risk-taking towards organisational performance of Internet business in Malaysia. As such, this article includes a discussion of the background and the uniqueness of the Internet business and highlighting the role of entrepreneurial strategy-making (ESM) dimensions that have a relationship towards organisational performance of Internet business. The paper concludes with implementation of effective strategy-making that can benefit the Internet entrepreneur in future.Â